Beyond Schweitzer and the psychiatrists: Jesus as fictive personality - Capps, Donald (HTS teologiese studies, 2003)
Albert Schweitzer and the psychiatric studies of Jesus that he critiqued in 1913 shared the belief that Jesus identified himself as the coming Messiah. Unlike the psychiatrists, however, Schweitzer did not therefore judge Jesus to have been delusional. This article concurs with Schweitzer on the grounds that “ideas of reference” were a common feature of the religious milieu in which Jesus lived. It introduces the psychoanalytic concept of the “fictive personality” as relevant to Jesus’ identification of himself as the coming Messiah. In contrast to delusional theories, this concept emphasizes the positive uses of such identifications, especially as a means of self-empowerment.